2012
DOI: 10.1016/j.phrs.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa intake attenuates oxidative stress associated with rat adjuvant arthritis

Abstract: 23 24Cocoa contains flavonoids with antioxidant properties. The aim of this study was to 25 ascertain the effect of cocoa intake on oxidative stress associated with a model of 26 chronic inflammation such as adjuvant arthritis. Female Wistar rats were fed with a 5 or 27 10% cocoa-enriched diet or were given p.o. a quercetin suspension every other day for 28 10 days. Arthritis was induced by a heat-killed Mycobacterium butyricum suspension. 29Reactive oxygen species (ROS) produced by macrophages, and splenic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Our findings support an important role of dietary cocoa to suppress pathological inflammatory events associated with neurological diseases, cardiovascular disease, diabetes, arthritis, and cancer . Our observed changes in protein expression within the upper spinal cord are likely the result of direct effects of cocoa metabolites since dietary plant flavonoids and sterols can cross the blood brain barrier, accumulate in the brain, and modulate neural function .…”
Section: Discussionsupporting
confidence: 77%
“…Our findings support an important role of dietary cocoa to suppress pathological inflammatory events associated with neurological diseases, cardiovascular disease, diabetes, arthritis, and cancer . Our observed changes in protein expression within the upper spinal cord are likely the result of direct effects of cocoa metabolites since dietary plant flavonoids and sterols can cross the blood brain barrier, accumulate in the brain, and modulate neural function .…”
Section: Discussionsupporting
confidence: 77%
“…The dietary flavonoid quercetin is thought to promote health, partly due to its ability to act as an antioxidant against ROS (Hertog and Hollman, ; Ramos‐Romero et al ., ) and to inhibit xanthine oxidase (XO; Zhu et al ., ). This compound decreases oxidative stress, improves the antioxidant status and inhibits liver cell apoptosis in STZ‐induced type 1 diabetic rats (Dias et al ., ; Babujanarthanam et al ., ; Bakhshaeshi et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study of Jia et al revealed that short-term consumption of a cocoa product lowered serum levels of LDL-cholesterol and TC (42) . In addition, a growing body of evidence from both in vitro studies and animal studies also demonstrated the antidyslipidaemic and anti-inflammatory effects of cocoa and cocoa flavonoids (43)(44)(45) . These favourable effects on the lipid profile might be explained by the reduction in the hepatic activity of 3-hydroxy-3-methlyglutaryl-coenzyme reductase, the limiting enzyme of cholesterogenesis (46) .…”
Section: Discussionmentioning
confidence: 99%